Multiuser detection and code timing estimation for CDMA systems - Li, Zhengyu. (2008)
This thesis is concerned with DS-CDMA systems operating over flat-fading channels with additive white Gaussian noise. It covers two different research areas: near-far resistant multiuser detection and robust code timing estimation.